Il simulacro del pensiero : La filosofia di Gilles Deleuze e il rovesciamento del platonismo - Gambaro, Giacomo (Scenari, 2021)
This essay tries to show the relevance of the concept of “simulacrum” in Gilles Deleuze’s work entitled “Plato and the Simulacrum”. Moving from Deleuze’s reformulation of Nietzschean goal of overthrowing Platonism, the path attempts to put in value the relationship between simulacrum and eternal return. For Deleuze, this relationship permits the constitution of the univocity of being. On the one hand the movement of simulacrum realizes the destabilization of platonic fundament, on the other hand the paradoxical circularity of eternal return dismantles the tendency to reconstruct hierarchical divisions between beings. Finally, the perspective of univocity develop the transformation of the statue of philosophy in the direction of the experience of difference.